Political disquisitions, or, An enquiry into public errors, defects, and abuses : Illustrated by, and established upon facts and remarks, extracted from a variety of authors, ancient and modern : calculated to draw the timely attention of government and people to a due consideration of the necessity and the means of reforming those errors, defects and abuses, of restoring the Constitution and saving the state. - Burgh, James, 1714-1775. (Tufts University. Tisch Library., 2015)
Volumes 1 and 2 of 3.; 1 online resource (3 volumes); V. 1 and 2 were published anonymously; authorship is attributed to James Burgh. Cf. ESTC(RLIN); NUC pre-1956.; Title page of v. 3 has author statement reading: "By J. B., Gent., author of The dignity of human nature, and other tracts."; With a half-title reading: Political disquisitions &c.; Errata: p. [9], 2nd sequence (v. 1-2).; Bookseller's advertisements: [2] p., final sequence of v. 3.; Index: [40] p., 3rd sequence of v. 3.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English short title catalogue T69213; Indexed in: NUC pre-1956,v. 85, p. 156